Environment-friendly degradable modified composite material, preparation method and application

By regulating the ratio of PBAT, PLA and natural plant fibers, and introducing degradable polyester elastomers and modified nanosilicon dioxide, the shortcomings of biodegradable plastics in terms of mechanical properties, degradation properties and compatibility are solved, and materials with high strength, flexibility and multifunctional characteristics are achieved to meet the application needs of multiple fields.

CN119661999AInactive Publication Date: 2025-03-21SHANXI HUAYANG BIODEGRADABLE NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411950483.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing biodegradable plastics have shortcomings in mechanical properties, degradation properties and compatibility, and cannot meet the needs of high strength, flexibility and multifunctional materials.

Method used

By accurately controlling the ratio of PBAT, PLA and natural plant fibers, and introducing degradable polyester elastomers and modified nanosilicon dioxide, the mechanical properties, degradation properties and processing properties of the materials are improved.

Benefits of technology

It realizes the high strength, flexibility and multifunctional characteristics of the material, meets the application needs of many fields such as packaging bags, disposable tableware and agricultural mulching, and has a stable and environmentally friendly degradation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661999A_ABST
    Figure CN119661999A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biodegradable materials, and particularly relates to an environment-friendly degradable modified composite material, a preparation method and application. The material comprises PBAT, PBS, PLA, an inorganic mineral filler, natural plant fibers, PBAT-PTMO, nano-silica, an auxiliary agent and a plasticizer. In the preparation process, PLA is prevented from being hydrolyzed in vacuum drying, calcium carbonate and nano silicon dioxide are preheated and activated, natural plant fibers are dispersed through steam explosion and ethanol treatment, and raw material pretreatment comprises high-speed mixing and agglomeration breaking and medium-speed secondary premixing so as to realize uniform distribution. The co-rotating twin-screw extruder accurately controls the temperature, the speed, the rotating speed and the length-diameter ratio, and ensures melting plasticizing, uniform mixing and stable extrusion molding. According to the invention, by adopting accurate proportioning of multiple raw materials and a modification treatment process, the properties of mechanics, degradation, processing and the like of the material are synergistically improved, and the material is widely applied to multiple fields such as packaging bags, disposable tableware and agricultural plastic mulching films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable materials, and specifically relates to an environmentally friendly degradable modified composite material, a preparation method and application thereof. Background Art

[0002] The widespread use of plastic products has become an indispensable part of modern life, however, the environmental problems it causes are becoming increasingly serious. Due to its structural characteristics, traditional plastics are difficult to degrade in the natural environment. The long-term accumulation of a large amount of waste plastics has led to the deterioration of soil quality, aggravated water pollution, and the destruction of the balance of the ecosystem, posing a huge threat to the earth's ecological environment. According to relevant research reports, hundreds of millions of tons of plastic waste are generated worldwide each year, and this number is rising year by year. In this context, the development of efficient and environmentally friendly degradable plastics has become an urgent task for global scientific research and industry to replace traditional plastics, alleviate the increasing pressure of environmental pollution, and achieve sustainable development goals.

[0003] At present, in the field of research and development of biodegradable plastics, polylactic acid (PLA) and polybutylene adipate / terephthalate (PBAT) have attracted much attention and are widely used. PLA has high hardness and strength, providing good structural support for products, but due to its high glass transition temperature, the brittleness of the material is significantly increased, and it is easy to break and damage when subjected to external impact, which greatly limits its application in occasions with high toughness requirements. Although PBAT exhibits excellent flexibility and processing performance and can meet the needs of various molding processes, the film made from it performs poorly in terms of stiffness and transparency, and cannot meet the strict requirements for material appearance and physical properties in specific fields such as high-end packaging and optical displays. For example, Patent Document 1 discloses a fully biodegradable plastic composite modified material suitable for film bags and its preparation method (publication number: CN113956623A). The patent uses direct blending of PBAT and PLA to combine the advantages of both to a certain extent. However, since polylactic acid (PLA) has high strength but high brittleness, and polybutylene adipate / terephthalate (PBAT) is flexible but has weak film performance, the simple blending of the two has poor compatibility due to differences in molecular structure and cannot synergistically improve performance. At the same time, the uniformity of the dispersion of fillers in the matrix is ​​difficult to guarantee, which further weakens the comprehensive performance of the material and cannot meet the market demand for multifunctional materials with high strength, good flexibility, stiffness, etc. Patent document 2 discloses a biodegradable mulch film and a preparation method thereof (publication number: CN105542423A). Although PBAT-PTMO is introduced as a degradable polyester elastomer to improve flexibility and elasticity and reduce brittleness, the mulch film degrades too quickly and degrades rapidly within 75 days. It cannot meet the mulch film covering time requirements of crops with long growth cycles (such as corn, cotton and other crops with a growth period of more than 90 days), resulting in the lack of mulch film protection during the critical growth period of crops, affecting yield and quality, and limiting the large-scale promotion and application of biodegradable mulch films. In addition, its technical solution does not provide effective technical reference value for solving key technical problems such as compatibility issues between PBAT and PLA, improving filler dispersibility, balancing material mechanics and degradation properties, and giving materials multifunctional properties, and further research is still needed.

[0004] However, when natural plant fibers are used to reinforce degradable plastics, the tightness of the bond with the matrix material has always been a key technical problem. Untreated fibers are incompatible with the matrix due to their surface properties, weak interfacial bonding, hindered stress transfer, limited improvement in mechanical properties and prone to interface separation. Existing treatment methods often have a single effect or are complex and difficult to control. They cannot accurately optimize the interaction between fiber properties and reinforced interfaces, and it is difficult to give full play to the advantages of fiber reinforcement, toughening and synergistic degradation, resulting in insufficient tensile strength, impact resistance and degradation stability of the material, further affecting its application prospects in high-load bearing, which limits the performance upgrade and application expansion of degradable materials.

[0005] In response to these problems, researchers have begun to explore new modification methods, such as using nanofillers for reinforcement and improving the compatibility of PLA and PBAT through graft copolymerization. However, these methods only improve certain mechanical properties of the material, and there are disadvantages such as the failure to achieve synchronous improvement in degradation rate, which makes it difficult for biodegradable plastics to meet the needs of complex application scenarios. Therefore, how to break through the existing component framework design system and at the same time, through modification processes, combine the advantages of different types of polymers, and study new biodegradable plastics to show broader application prospects, it is expected to achieve a win-win situation of environmental friendliness and economic benefits in the near future. Summary of the invention

[0006] In view of the many defects of existing biodegradable plastics, the present invention aims to develop a new environmentally friendly degradable modified composite material, by accurately controlling the proportions and characteristics of a variety of raw materials, and introducing innovative modification and treatment processes to deeply optimize the performance of the material. Specifically, the focus is on overcoming the compatibility problem of PBAT and PLA, improving the dispersion of fillers in the matrix, enhancing the mechanical properties, degradation properties and processing properties of the material, and at the same time giving the material multifunctional properties such as good flexibility, stiffness, transparency, printability, etc., to expand its wide application in packaging bags, disposable tableware, agricultural mulch films and other fields, and fully meet the increasingly stringent performance standards and functional demands of different industries for environmentally friendly degradable materials, fill the gaps in the existing technology in the field of high-performance degradable plastics, and lead the innovative development and upgrading transformation of the biodegradable materials industry. Based on this, the present invention provides an environmentally friendly degradable modified composite material, preparation method and application.

[0007] To achieve the above object, the present invention adopts the following technical scheme: an environmentally friendly degradable modified composite material, which is mainly made of the following raw materials in percentage by weight: polybutylene adipate / terephthalate: 10%-50%; polybutylene succinate: 10%-30%; polylactic acid: 10%-60%; inorganic mineral filler: 0%-30%; natural plant fiber: 3%-5%; degradable polyester elastomer: 5%-10%; nano silicon dioxide: 1%-3%; additives: 4%-6%; plasticizer: 0.5%-1.5%; the natural plant fiber is preferably selected from the group consisting of: The composite material is placed in a steam explosion tank and an alkali solution soaking reactor for steam explosion and alkali solution soaking modification treatment to improve the mechanical meshing effect and chemical bonding force with the matrix material, and improve the tensile and impact resistance of the material; the degradable polyester elastomer is poly(1,4-butylene adipate diol)-co-poly(butylene terephthalate diol) to enhance the flexibility and impact resistance of the material; the nano-silica is surface-modified with a silane coupling agent KH550 in an ultrasonic cleaning machine to improve the dispersibility and compatibility of the nano-silica in the matrix and improve the comprehensive performance of the composite material.

[0008] As a further explanation and limitation of the above technical solution, the plasticizer is tributyl citrate, which is used to optimize the material processing performance and flexibility and ensure the foldability and durability of the product.

[0009] As a further supplementary explanation of the above technical solution, the natural plant fiber is any one of cotton fiber, hemp fiber, bamboo fiber, coconut shell fiber and corn straw fiber.

[0010] As a further supplement to the above technical solution, the explosion pressure in the steam explosion treatment is 1.5-2.5 MPa, the maintenance time is 10-15 seconds, and the fiber length after treatment is 0.5-2 mm, so as to improve the fiber dispersion and the interface bonding strength of the composite material.

[0011] As a further supplement to the above technical solution, the alkali solution concentration in the alkali solution soaking treatment is 3%-5%, the soaking time is 1-2 hours, and then it is rinsed with deionized water to neutrality and dried to further remove impurities and pectin on the fiber surface and increase the roughness of the fiber surface.

[0012] As a further explanation and limitation of the above technical solution, the auxiliary agent is maleic anhydride, 2-imidazolidinone and styrene and glycidyl acrylate copolymer, and the mass ratio of the three is 0.4:0.4:1.

[0013] As a further supplement to the above technical solution, the dosage of the silane coupling agent KH550 is 8%-12% of the mass of nano-silicon dioxide, the working ultrasonic power of the ultrasonic cleaning machine is 300-500W, the processing time is 15-25 minutes, and the ultrasonic cavitation effect cooperates with the coupling agent to make the coupling agent more evenly coat the particle surface, forming a stable chemical bonding layer, enhancing compatibility with the matrix and interfacial adhesion, improving the tensile strength, elongation at break and thermal stability of the composite material, inhibiting the generation of material defects caused by nano-particle agglomeration, and ensuring the uniformity of the material microstructure and the consistency of macroscopic performance.

[0014] As a further supplement to the above technical solution, the inorganic mineral filler is any one or more combinations of talc, calcium sulfate, calcium silicate and calcium carbonate, and its particle size is 800 mesh-3000 mesh. This particle size range is conducive to its uniform dispersion in the matrix, reducing defects caused by agglomeration, enhancing the mechanical properties and stability of the material, ensuring that the degradation process is uniform, and avoiding the degradation rate and product life due to local structural differences.

[0015] A method for preparing an environmentally friendly degradable modified composite material comprises the following steps: S1 Raw material pretreatment: Place polylactic acid in a vacuum drying oven and maintain it at 45-50°C for 4-5 hours to remove moisture and volatiles to prevent hydrolysis from causing molecular chain breakage and reducing performance; preheat inorganic mineral fillers and nano-silicon dioxide at 100-110°C for 30-35 minutes to improve their dispersibility and reactivity in the mixed system; natural plant fibers are pretreated by steam explosion and mixed with 60%-70% ethanol solution for 20-30 minutes to achieve initial dispersion and surface infiltration, which is conducive to subsequent uniform mixing with other raw materials; S2 premixing: Weigh polybutylene adipate / terephthalate, dried polylactic acid, polybutylene succinate, preheated inorganic mineral filler, treated flax fiber, degradable polyester elastomer, modified nano-silica, tributyl citrate and additives in proportion and put them into a high-speed mixer, mix them at a high speed of 500-900 rpm for 7-8 minutes, use strong shear force to break the agglomeration of the raw materials, and preliminarily evenly disperse the components; S3 secondary premixing: Add the additives again and premix for 5-6 minutes at a medium speed of 240-260rpm to optimize the uniformity of raw material distribution, ensure that the additives fully interact with the raw materials, and improve the compatibility of the system; S4 Melting, plasticizing and molding: The mixed material is fed into a co-rotating twin-screw extruder, and the screw temperature is set at 60-180°C, the screw speed is 150-250rpm, and the screw aspect ratio is 48:1-56:1. Under this condition, the raw materials are fully melted, plasticized, mixed evenly, and extruded stably; the extruded strips are air-cooled and drawn, cut into pellets with a spacing of 4.6-4.8mm, vibrated and screened, and transported to the finished product silo.

[0016] An environmentally friendly biodegradable modified composite material is used in the preparation of packaging bags, disposable tableware, and agricultural mulch films. During the application process, the composite material can meet the use requirements in different scenarios by accurately controlling the degradation rate, while reducing the impact on the environment. In addition, its excellent mechanical properties and stability ensure the safety and durability of the product during use, providing strong support for promoting the widespread application of green and environmentally friendly materials.

[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention uses polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS), polylactic acid (PLA) and natural plant fibers as raw materials. PBAT, PLA and natural plant fibers are synergistically degraded and cooperate with each other to ensure smooth and continuous degradation. Plant fibers provide microbial attachment sites and nutrition to accelerate degradation. The degradation products do not affect the ecological balance of the environment and there is no risk of secondary pollution. In addition, the added additives maleic anhydride, 2-imidazolidinone and styrene and glycidyl acrylate copolymer are non-toxic and degradable, and do not produce difficult-to-treat pollutants; the plasticizer uses tributyl citrate, which is a green and environmentally friendly type with good biocompatibility and can be degraded and absorbed, ensuring the overall degradability and environmental friendliness of the material.

[0018] 2. The present invention redesigns the ratio of PBAT and PLA, and adds an appropriate amount of degradable polyester elastomer (PBAT-PTMO) to form a new matrix with both strength and flexibility. After steam explosion and alkali soaking, the natural plant fiber is tightly combined with the matrix, which greatly enhances the tensile and impact resistance of the material. Nano-silica is modified with KH550 to optimize the material microstructure, improve tensile strength, elongation at break and thermal stability, and successfully solve the material defect problem caused by particle agglomeration.

[0019] 3. In the raw material pretreatment stage, the present invention has low energy consumption and less pollution in PLA vacuum drying, inorganic mineral filler and nano-silicon dioxide preheating and natural plant fiber ethanol infiltration; process optimization during processing improves material mixing and melting efficiency, reduces energy consumption and waste emissions, reduces carbon footprint and environmental interference in the production stage, conforms to the trend of green manufacturing, and reduces the environmental cost of the material throughout its life cycle. Among them, the premixing and secondary premixing process of the high-speed mixer greatly optimizes the dispersibility and reactivity of the raw materials and improves the compatibility of the system.

[0020] 4. The materials developed by the present invention have excellent mechanical properties and good wear resistance. The products such as disposable tableware, packaging bags, and agricultural mulch films have a long service life, reducing the amount of waste generated due to damage and replacement frequency, indirectly alleviating resource consumption and waste disposal pressure, maximizing environmental benefits from the perspective of the entire product life cycle, improving the comprehensive environmental value of the product, and providing support for sustainable consumption and production models. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a comparison chart of the test performance of each embodiment of the present invention and the control group; Figure 2 This is a comparison diagram of the dispersion state of the pellets before and after modification with nano-silicon dioxide in the present invention; Figure 3 It is a scatter diagram of the relationship between the tensile strength and elongation at break of the material in different embodiments and the control group; Figure 4is a graph showing the relationship between material degradation time and mass loss rate for different embodiments and a control group; Figure 5 This is a physical picture of the property-preserving biodegradable modified composite material produced by the preparation process of the present invention; Figure 6 It is the change diagram of the characteristic peak intensity of the FTIR spectrum of the present invention and the comparative patent; Figure 7 The concentration change diagram of the main degradation products detected by GC-MS in the present invention and the comparative patent at 6 months and 12 months; Figure 8 A bar chart comparing the energy consumption of the present invention and the comparative patent; Fig. 9 The figure is a bar chart comparing waste emissions of the present invention and the comparative patent. DETAILED DESCRIPTION

[0022] In order to further illustrate the technical solution of the present invention, as shown in the attached Figures 1 to 9 As shown, in combination with the entire project development process, aiming at the application of the modified composite material in the fields of packaging bags, disposable tableware, and agricultural mulch films, we further illustrate the present invention by designing 6 embodiments and 3 control groups.

[0023] 1. Material composition selection and ratio design 1. Raw material preparation The environmentally friendly degradable modified composite material developed by the present invention has been determined through preliminary research, and the proportions of various raw materials are as follows: PBAT (10%-50%), PBS (10%-30%), PLA (10%-60%), inorganic mineral filler (0%-30%, 800-3000 mesh), natural plant fiber (3%-5%), degradable polyester elastomer (PBAT-PTMO, 2%-4%), nano-silicon dioxide (1%-3%), additives (4%-6%, containing a specific proportion of maleic anhydride, 2-imidazole ketone and styrene and glycidyl acrylate copolymer), plasticizer (tributyl citrate, 0.5%-1.5%). The inorganic mineral filler is any one of talc, calcium sulfate, calcium silicate and calcium carbonate, and the specific and appropriate inorganic minerals can be selected according to the purpose of the product. This ratio has been optimized through systematic research and repeated tests, and the various components work synergistically to lay the foundation for the high performance of the material.

[0024] (II) Fiber modification Natural plant fibers (such as flax, bamboo, cotton, coconut shell, corn straw fibers) are treated by steam explosion (pressure 1.5-2.5MPa, maintain 10-15 seconds, 0.5-2mm fiber) and alkali solution soaking (3%-5% alkali solution, 1-2 hours, then rinse and dry). Steam explosion initially changes the fiber structure and improves dispersibility; alkali solution soaking deeply removes impurities, increases roughness, and strengthens chemical activity. The combination of the two greatly enhances the mechanical meshing and chemical bonding between the fiber and the matrix, effectively improving the tensile and impact resistance of the material.

[0025] (III) Nano-silicon dioxide treatment Nano-silica is modified by using silane coupling agent KH550 (8%-12% of its mass) with ultrasound assistance (300-500W, 15-25 minutes). The ultrasonic cavitation effect cooperates with the coupling agent to make the coupling agent evenly coat the particles and form a stable chemical bonding layer, which significantly improves its dispersion and compatibility in the matrix, optimizes the microstructure of the composite material, improves the comprehensive properties such as tensile strength, elongation at break, thermal stability, and inhibits material defects caused by agglomeration.

[0026] 2. Material preparation process S1 Raw material pretreatment: PLA is vacuum dried at 45-50°C for 4-5 hours to remove water and prevent hydrolysis; inorganic mineral fillers and nano-silicon dioxide are preheated at 100-110°C for 30-35 minutes to enhance the dispersion reaction activity; natural plant fibers are steam exploded and mixed with 60%-70% ethanol solution for 20-30 minutes to create good conditions for subsequent uniform mixing.

[0027] S2 pre-mixing: weigh the raw materials according to the proportion and put them into the high-speed mixer, mix them at a high speed of 500-900rpm for 7-8 minutes, use the strong shear force to break the agglomeration of the raw materials, and initially achieve uniform dispersion of the various components, laying the foundation for uniform and stable material performance.

[0028] S3 secondary premixing: Add the additives again and premix for 5-6 minutes at a medium speed of 240-260rpm to optimize the uniformity of raw material distribution, ensure that the additives fully interact with the raw materials, improve the compatibility of the system, and improve the control of material performance.

[0029] S4 Melting plasticization and molding: The mixed material is fed into a co-rotating twin-screw extruder, melted and plasticized, uniformly mixed, and stably extruded under the conditions of screw temperature 60-180°C, screw speed 150-250rpm, and aspect ratio 48:1-56:1. The extruded strips are air-cooled and drawn, cut into pellets with a spacing of 4.6-4.8mm, vibrated and screened, and transported to the finished product silo.

[0030] As attached Figure 5As shown, in the finished product silo, the pellets are packaged by a semi-automatic pellet packaging machine. After sealing, these packaged materials can be sold to customers in the market or directly used in the downstream product production process.

[0031] At present, our workshop has vertical mixers, express bag film blowing machines, ground film blowing machines, single-layer film blowing machines, ABA film blowing machines, various bag making machines, slitting machines, and low-temperature granulation machines. The modified masterbatch is used as the raw material, after stirring, it is blown with a degradable film blowing machine, printed with environmentally friendly water-based ink (most air column cushioning bags do not need printing), and finally processed by hot cutting and forming by a bag making machine to produce biodegradable film bags. After stirring, the special material for ground film is blown with an ABC three-layer co-extrusion film blowing machine, and then cut to produce biodegradable ground film.

[0032] In addition, the existing film bag product workshop uses the degradable modified composite masterbatch developed by the present invention as the production raw material according to the production plan or customer order specifications, and produces qualified fully biodegradable customized products and packages them through processes such as film blowing, printing, winding, and bag making. It mainly produces PE and fully biodegradable plastic products, including express bags, ground films, pet bags, garbage bags, seedling bags, shopping bags, etc.

[0033] 3. Implementation Example Design and Key Performance Indicator Testing To further improve the performance of the materials, we have conducted strict quality control and performance testing. By testing key indicators such as the tensile strength, elongation at break, and degradation time of the pellets, we ensure that each batch of composite materials meets high standards.

[0034] In response to the diverse needs of downstream products, we have developed composite materials with different proportions through different implementation methods to meet the market demand for environmentally friendly and high-performance materials.

[0035] 1. Experimental design As attached Figure 1 As shown in the figure, we have built a multi-dimensional testing system: according to the ASTM series standards, we use an electronic universal testing machine to measure tensile strength and elongation at break; the soil burial method is used to evaluate degradation performance; according to the ASTMD1238 standard, the melt flow rate is measured and the molding shrinkage is calculated to evaluate processing performance; differential scanning calorimetry and thermogravimetric analysis are used to analyze thermal properties; scanning electron microscope is used to observe microstructure. Each test is precisely designed and strictly regulated to ensure a comprehensive and accurate evaluation of material performance.

[0036] (II) Test results of the embodiment Embodiment 1

[0037] Material composition ratio: In this embodiment, the mass percentage of each raw material is respectively polybutylene adipate / terephthalate (PBAT) 10%, polybutylene succinate (PBS) 10%, polylactic acid (PLA) 60%, inorganic mineral filler (talc 15%, calcium silicate 5%) 20% (particle size 800 mesh-3000 mesh), natural plant fiber (bamboo fiber) 3%, degradable polyester elastomer (polybutylene adipate-1,4-diol diol-co-polybutylene terephthalate diol) 5%, nano silicon dioxide 1%, additive (maleic anhydride, 2-imidazole ketone and styrene and glycidyl acrylate copolymer mass ratio 0.4:0.4:1) 4%, plasticizer (tributyl citrate) 0.5%. Under this ratio, PLA accounts for a high proportion, providing a good hardness and strength foundation for the material, while PBAT and PBS give a certain flexibility, and the various components work together to form the basic system of the composite material.

[0038] Performance: The composite material is suitable for degradable blister lunch boxes. In terms of mechanical properties, the tensile strength can reach about 47MPa, and the elongation at break is about 22%. The bamboo fiber is tightly combined with the matrix after steam explosion and alkali solution soaking modification, and the nano-silicon dioxide is strengthened to enable the lunch box to withstand a certain external force without breaking easily, meeting the strength and toughness requirements of daily use. In terms of degradation performance, under soil burial conditions, it begins to degrade significantly in about 6 months, and a high degree of degradation can be achieved in about 12 months. PLA dominates the degradation process, and PBAT, PBS and bamboo fiber provide microbial attachment sites to ensure smooth and continuous degradation. The processing performance is good, the melt flow rate is moderate, and it is easy to blister mold. The molded lunch box has high dimensional accuracy and good appearance quality. The plasticizer optimizes the processing performance to make the surface smooth. The lunch box also has a certain heat resistance, which can meet the temperature requirements of general food packaging, and it is environmentally friendly and can be naturally degraded to reduce environmental pollution. After use, it can be composted together with food residues, etc., which is in line with the development trend of environmentally friendly catering. Embodiment 2

[0039] Material composition ratio: The mass percentage of each raw material in this embodiment is PBAT 12%, PBS 8%, PLA 55%, inorganic mineral filler (calcium sulfate) 15% (particle size 800 mesh-3000 mesh), natural plant fiber (hemp fiber) 4%, degradable polyester elastomer 7%, nano silicon dioxide 2%, additive 5%, plasticizer 1%. Among them, PBAT and PBS have a moderate ratio, balancing the flexibility and strength of the material, PLA provides structural support, and calcium sulfate filler enhances performance. Each component complements each other to build the material composition.

[0040] Performance: When used for degradable injection-molded lunch boxes, its mechanical properties are tensile strength of about 53MPa and elongation at break of about 8%. After modification, the hemp fiber enhances the bonding strength with the matrix, and the combined effect with calcium sulfate makes the injection-molded lunch box have good impact resistance, which can effectively resist collision and extrusion during use and transportation. The degradation time in the soil is about 5.5 months. The reasonable ratio of PBAT, PBS and PLA and the synergistic effect of hemp fiber ensure that the lunch box can be degraded quickly after the use cycle, reducing the long-term impact on the environment. The processing process has good fluidity and is easy to injection mold. It can produce lunch box products with complex shapes and high precision requirements. The addition of additives improves the compatibility of the system, ensures that the components are evenly dispersed, and improves the stability of product quality. The surface hardness of the lunch box is moderate, not easy to scratch, and has good chemical resistance, which can prevent chemical reactions when in contact with food. The appearance texture is good and can meet consumers' requirements for product appearance. Embodiment 3

[0041] Material composition ratio: The material composition ratio of this embodiment is PBAT 50%, PBS 25%, PLA 15%, inorganic mineral filler (calcium carbonate) 2% (particle size 800-3000 mesh), natural plant fiber (flax fiber) 5%, degradable polyester elastomer 8%, nano silicon dioxide 3%, additive 6%, plasticizer 1.5%. The high content of PLA ensures strength, PBAT, PBS and other ingredients synergistically improve flexibility and comprehensive performance, and flax fiber further enhances material properties. Each component works in this ratio.

[0042] Performance: Suitable for ordinary agricultural mulch. Its tensile strength is about 34MPa, elongation at break is about 330%, and puncture resistance is excellent. After treatment, the flax fiber is tightly bonded to the substrate, which enhances the mechanical strength of the mulch, so that it can resist puncture from stones and farm tools in the soil during laying and use, reducing the possibility of damage. The degradation time in the soil is about 5 months, which meets the growth cycle requirements of one season of crops. The synergistic degradation of PBAT, PBS, and PLA and the microbial attachment points provided by flax fibers ensure timely degradation without polluting the soil. In terms of optical properties, the light transmittance exceeds 86%, the haze is about 7%, and it effectively transmits sunlight, reduces light scattering, improves light utilization, and provides sufficient light conditions for crop growth. The surface has a certain wear resistance, which can resist the friction of soil particles to a certain extent, prolong the service life of the mulch, has good flexibility, is easy to lay, can fit closely to the soil surface, reduce air circulation, and play a better role in heat preservation and moisture retention. Embodiment 4

[0043] Material composition ratio: The raw materials in this embodiment are PBAT 45%, PBS 30%, PLA 18%, inorganic mineral filler (calcium carbonate) 4% (particle size 800-3000 mesh), natural plant fiber (corn straw fiber) 3%, degradable polyester elastomer 9%, nano silicon dioxide 2%, additive 5%, plasticizer 1%. The proportion of PBAT and PBS is adjusted to improve flexibility and help withstand impact, PLA and other ingredients ensure strength, corn straw fiber enhances overall performance, and each ingredient together builds a material system.

[0044] Performance: When used for functional mulch (such as weed control mulch or anti-fog drop mulch, etc.), taking weed control mulch as an example, the tensile strength is about 36MPa, the elongation at break is about 350%, and the corn straw fiber enhances the tensile and impact resistance, can withstand the transportation and handling of a certain weight of goods, and is not easily damaged during the laying and use of the mulch. The degradation time in the natural environment is about 6.5 months. The combination of PBAT, PBS and PLA and the role of corn straw fiber ensure gradual degradation and reduce environmental pressure. The weed control mulch adds an appropriate amount of herbicidal ingredients, which can be slowly released after covering, inhibiting the growth of weeds, reducing the competition of weeds for crop nutrients and water, and increasing crop yields. At the same time, the mulch has good flexibility, which is easy to lay and fit the ground to ensure the weed control effect. If it is an anti-fog drop mulch, special surface treatment or the addition of anti-fog drop agents can effectively prevent water droplets from condensing on the surface of the film to form droplets, maintain the transparency of the film surface, improve the utilization rate of light, and promote the growth of crops. Embodiment 5

[0045] Material composition ratio: The raw material ratios in this embodiment are PBAT 27%, PBS 18%, PLA 25%, inorganic mineral filler (calcium carbonate) 24% (particle size 800-3000 mesh), natural plant fiber (cotton fiber) 4%, degradable polyester elastomer 10%, nano silicon dioxide 2%, additive 6%, plasticizer 1.5%. The high content of PBAT and PBS makes the material more flexible, PLA guarantees the basic strength, cotton fiber is closely combined to enhance the overall strength, and the various components work synergistically to construct the material.

[0046] Performance: Suitable for printing outer packaging bags. The tensile strength exceeds 38MPa, the elongation at break is about 380%, the strength and toughness are high, the cotton fiber is tightly combined with the matrix after treatment, and it is not easily damaged by daily external forces, which can meet the needs of packaging general items, such as daily necessities, clothing, etc. The degradation time in soil or compost environment is about 7 months. The synergy of PBAT, PBS, PLA and the microbial action sites of cotton fibers ensure rapid degradation, which meets environmental protection requirements. The surface is easy to print, the ink has strong adhesion, the printed pattern is clear and firm, and exquisite pattern design and text printing can be carried out to meet personalized packaging needs and enhance product added value. It has good moisture-proof properties, which can effectively protect the items in the package from the influence of humid environment. It is flexible and easy to fold and store, saving transportation and storage space. Embodiment 6

[0047] Material composition ratio: In this embodiment, the raw materials are PBAT 25%, PBS 16%, PLA 28%, inorganic mineral filler (talcum powder) 30% (particle size 800-3000 mesh), natural plant fiber (coconut shell fiber) 3.5%, degradable polyester elastomer 9%, nano silicon dioxide 1.5%, additive 5%, plasticizer 1%. PBAT, PBS and PLA and other ingredients balance strength and flexibility, coconut shell fiber enhances mechanical properties, and each component works in proportion.

[0048] Performance: It can be used for food-grade packaging bags. The tensile strength is about 35MPa, the elongation at break is about 340%, and the tensile and tear resistance are good. The special structure and modification of coconut shell fiber make it firmly bonded to the matrix, withstand the test of agricultural production environment, and can effectively protect the integrity of food during transportation and storage. The degradation time in the soil is about 6 months, which matches the growth cycle of crops. The reasonable ratio of PBAT, PBS, PLA and the role of coconut shell fiber ensure timely degradation after the function is completed, without affecting the soil structure and crop growth. It has good barrier properties, can prevent the penetration of gases and substances such as oxygen and moisture, extend the shelf life of food, and ensure the freshness and quality of food. It meets the safety standards of food contact materials, is non-toxic and tasteless, will not cause pollution to food, and ensure food safety. At the same time, the material has good flexibility and weather resistance, and can adapt to different climatic conditions and transportation environments.

[0049] 3. Control group setting Control group 1: After removing PBAT-PTMO from Example 1, when used to degrade blister lunch boxes, the tensile strength of disposable tableware dropped to 26MPa, the elongation at break was reduced to 200%, the toughness and impact resistance dropped sharply, and microcracks appeared. This is because the removal of the degradable polyester elastomer significantly reduces the flexibility and impact resistance of the material, and it cannot effectively buffer external forces, causing the lunch box to be easily damaged when subjected to a small external force, unable to meet normal use requirements, and the appearance quality is also affected, and the surface may be uneven, affecting the aesthetics of the product. In addition, due to the removal of the degradable polyester elastomer, the structure and properties of the material are changed, making its degradation process slower, reaching more than 7 months.

[0050] Control group 2: Example 3 lacks natural plant fibers. When applied to ordinary agricultural mulch, the tensile strength is reduced to 24MPa, the elongation at break is reduced to 220%, and the mulch is mechanically weakened and easily damaged. Natural plant fibers play an important role in enhancing the mechanical strength of mulch. After their removal, the ability of the mulch to resist puncture by stones and farm tools in the soil during laying and use is significantly reduced, and it is prone to damage, affecting the performance of functions such as heat preservation, moisture retention and weed control. Moreover, the degradation time is extended to about 6 months, which cannot be well matched with the crop growth cycle, and may result in the mulch not being completely degraded in the later stage of crop growth, which has an adverse effect on the soil environment.

[0051] Control group 3: Example 5 did not use KH550 to modify nano-silica. When used to print outer packaging bags, the strength of the packaging bags was limited and there were agglomeration defects. The unmodified nano-silica was unevenly dispersed in the matrix and easily agglomerated, resulting in local stress concentration, which prevented the material strength from being fully exerted, and the tensile strength dropped to about 30MPa, and the elongation at break was about 300%. The printing performance was also affected, the ink adhesion decreased, and the printed pattern was easily blurred and faded, affecting the appearance of the packaging and the communication of information. In terms of degradation performance, since the agglomeration of nano-silica may affect the overall degradation process, the degradation time was extended to about 8 months.

[0052] As attached Figures 2 to 4As shown, we introduced three control group designs and conducted studies with Examples 1, 3, and 5, respectively, and we can draw the following conclusions: First, at the raw material level, by introducing natural plant fibers that have been steam exploded and soaked in alkali solution for degrading blister lunch boxes (Example 1), the matrix bonding strength can be enhanced, the tensile and impact resistance can be improved, and the limitations of traditional fiber use can be broken. Secondly, the addition of degradable polyester elastomer (PBAT-PTMO) compensates for the brittleness of PLA and optimizes the strength-toughness balance, such as in packaging bag applications. The effect is excellent. Finally, nano-silicon dioxide is ultrasonically modified by KH550 to improve dispersibility and compatibility, enhance comprehensive performance, and inhibit agglomeration defects. In terms of technology, fine pretreatment combined with high-speed-medium-speed mixing and precise extrusion parameters ensures uniform and stable materials, high product precision, excellent quality, excellent performance in multiple fields, high functional integration, and comprehensive improvement of material value and competitiveness.

[0053] 4. Environmental performance evaluation and analysis In order to verify the environmental advantages of the present invention over the comparative patents, this study prepared test sample materials based on the public data and preparation process of a fully biodegradable plastic composite modified material suitable for film bags and its preparation method (publication number CN113956623A), and conducted experimental analysis with the test sample materials prepared by the present invention.

[0054] 1. Analysis of degradation products We used Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectrometry (GC-MS) technology to analyze the products of the materials involved in the present invention and the comparative patents after degradation in a simulated natural environment through post-experimental methods. The simulated environment was set as soil burial (simulating farmland soil conditions, controlling temperature, humidity and microbial communities) and water immersion (simulating seawater environment, adjusting pH and oxygen content), and the degradation cycle was set to 3 months, 6 months, 12 months and 24 months, and degradation samples were collected regularly for testing.

[0055] As attached Figure 6 As shown, the FTIR spectrum shows the changes in the intensity of the carbonyl, ester bond, hydroxyl and carboxyl (in the present invention) and the characteristic peak containing benzene ring (comparative patent) of the material of the present invention and the comparative patent material during the degradation process, which intuitively presents the difference in the degradation process.

[0056] As attached Figure 7 As shown, the GC-MS detection comparison chart focuses on the concentration and relative abundance of the main degradation products at 6 months and 12 months, highlighting the benign transformation of the degradation products of the present invention and the incomplete degradation and harmful product generation of the comparative patents, providing a clear and visual basis for evaluating the environmental friendliness of the materials, and facilitating in-depth analysis of the material degradation mechanism and environmental impact.

[0057] 2. Energy consumption and waste emission assessment For the material preparation stage, this study calculated the energy consumption and waste emissions at each stage according to the production process. The entire process from raw material pretreatment, mixing processing to molding was monitored, and data was collected using energy consumption monitoring instruments and pollutant emission detection equipment. The energy consumption and waste indicators per unit output of the present invention and the comparative patent were compared to evaluate the environmental impact of the production process.

[0058] like Figure 8 As shown in the energy consumption comparison bar chart, the energy consumption difference between the material of the present invention and the comparative patent material in the raw material pretreatment, mixing and extrusion stages is clearly presented, and the energy-saving advantages of each link of the present invention are intuitively demonstrated. Fig. 9 As shown, the waste emission comparison bar chart accurately compares the waste materials, waste gas (VOCs and particulate matter), waste water and waste residue emissions of the two, highlighting the characteristics of the present invention with low waste emissions, good treatment effect and high resource recovery rate, which strongly proves the green manufacturing advantages of the present invention in the production link, helps to deeply understand the differences in the environmental performance of materials, and provides visual support for technology evaluation and improvement.

[0059] V. Analysis of Existing Technologies Through preliminary technical search, we found that Foshan Yueshengda New Materials Co., Ltd. submitted a fully biodegradable plastic composite modified material suitable for film bags and its preparation method on September 29, 2021 (publication number: CN113956623A). This public patent focuses on the combination of PBAT, PBS, PLA, calcium carbonate and specific additives to optimize the performance of film bags. The main ingredients and additives are similar to those of the present invention, and the preparation process is also similar. Therefore, taking this public patent as the prior art, we evaluate the differences between the present invention and the comparative patent from the perspective of technical issues, design ideas, and the material mechanism corresponding to the preparation process direction.

[0060] First, the present invention breaks through the existing component framework and introduces key elements such as natural plant fibers, degradable polyester elastomers (PBAT-PTMO) and modified nano-silica on the basis of the core components of common biodegradable plastics, PBAT, PLA and PBS. Natural plant fibers are double modified by steam explosion and alkali solution soaking. For example, bamboo fibers are used in disposable tableware (Example 1), which increases the tensile strength to 47MPa and reduces the elongation at break to 22%, far exceeding the traditional formula. This is due to its close combination with the matrix to optimize stress transfer. This innovative modification and combination method is unique in the field of biodegradable materials. PBAT-PTMO accurately compensates for the brittle defects of PLA, ensures a delicate balance of strength and toughness in the application of packaging bags (Examples 5 and 6) and disposable tableware (Examples 1 and 2), and provides a new idea for optimizing the mechanical properties of materials.

[0061] Second, the present invention is carefully designed in the pretreatment link. PLA is vacuum dried to prevent hydrolysis, calcium carbonate and nano-silicon dioxide are preheated to increase activity, and natural plant fiber is infiltrated with ethanol to promote dispersion, laying a solid foundation for subsequent mixing. This fine pretreatment is rare in the industry. In the mixing stage, high-speed (500-900rpm) strong shearing is used to break agglomerates, and then medium-speed (240-260rpm) is used for secondary optimization of distribution. The co-rotating twin-screw extruder accurately matches the raw material characteristics to ensure that the material is evenly melted, plasticized, and extruded stably. The product size accuracy and appearance quality are excellent. For example, the agricultural mulch film (Examples 3 and 4) has both good mechanical properties and optical properties. The preparation process is closely coordinated and deeply optimized in all links, which is in sharp contrast to the existing general process and shows outstanding substantive characteristics.

[0062] Third, after the above series of innovations, natural plant fibers modified with nano-silicon dioxide have comprehensively enhanced tensile, impact and bending properties, and have excellent performance in multiple application scenarios. For example, the tensile strength of the packaging bag (Example 5) exceeds 38MPa, and the elongation at break is about 380%. The disposable tableware (Examples 1 and 2) has both high strength and high toughness, which fully meets the needs of complex working conditions, opens up broad prospects for high-load applications of products, and achieves a major breakthrough in the balance between strength and toughness compared to traditional materials and similar patents, pushing the mechanical properties of biodegradable materials to a new level, demonstrating significant progress.

[0063] Fourth, through the synergistic effects of PBAT, PLA and natural plant fibers, the present invention allows disposable tableware (Examples 1 and 2) and mulch films (Examples 3 and 4) to stably degrade over their usage cycles, effectively avoiding the traditional plastic pollution dilemma and the problem of disordered degradation of some degradable materials, achieving a harmonious unity of environmental protection and performance, and leading a new trend in the precise regulation of the degradation performance of biodegradable materials. Compared with similar technologies, it has significant advantages in degradation stability and adaptability.

[0064] Fifth, the optical performance of the agricultural mulch film of the present invention is excellent and wear-resistant. For example, the light transmittance of the ordinary agricultural mulch film in Example 5 is 87% and the haze is 7%. Among them, the degradation time in the soil is about 5 months, which meets the growth cycle requirements of one season of crops. Therefore, from the selection of raw materials to the innovative design of the process, the present invention breaks through the functional limitations of traditional materials, helps to broaden the high-end application scenarios of biodegradable materials in multiple fields, and comprehensively enhances the comprehensive value and market competitiveness of the products.

[0065] VI. Conclusion In summary, the environmentally friendly biodegradable modified composite material designed by the present invention has been systematically and scientifically designed and rigorously tested, successfully overcoming the compatibility of PBAT-PLA and the dispersion of fillers, and achieving all-round optimization and innovation in mechanics, degradation, processing, thermal properties and microstructure. Multi-field implementation test and comparative analysis strongly support its wide applicability and excellent performance, providing innovative solutions for the upgrading of the biodegradable materials industry and meeting environmental protection needs, leading the new trend of sustainable material development, and promoting the green transformation process in multiple industries.

[0066] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An environmentally friendly degradable modified composite material, characterized in that: Mainly made of the following raw materials by mass percentage: Polybutylene adipate / terephthalate: 10%-50%; Polybutylene succinate: 10%-30%; Polylactic acid: 10%-60%; Inorganic mineral fillers: 0%-30%; Natural plant fiber: 3%-5%; Degradable polyester elastomer: 5%-10%; Nano silicon dioxide: 1%-3%; Additives: 4%-6%; Plasticizer: 0.5%-1.5%; The natural plant fiber is sequentially placed in a steam explosion tank and an alkali solution soaking reactor for steam explosion and alkali solution soaking modification treatment to improve the mechanical meshing effect and chemical bonding force with the matrix material and improve the tensile and impact resistance of the material; The degradable polyester elastomer is poly(1,4-butylene adipate glycol)-co-poly(butylene terephthalate glycol), which is used to enhance the flexibility and impact resistance of the material; The nano silicon dioxide is subjected to surface modification treatment with a silane coupling agent KH550 in an ultrasonic cleaning machine to improve the dispersibility and compatibility of the nano silicon dioxide in the matrix and enhance the comprehensive performance of the composite material.

2. The environmentally friendly biodegradable modified composite material according to claim 1, characterized in that: The plasticizer is tributyl citrate, which is used to optimize the material processing performance and flexibility and ensure the foldability and durability of the product.

3. The environmentally friendly degradable modified composite material according to claim 1, characterized in that: The natural plant fiber is any one of cotton fiber, hemp fiber, bamboo fiber, coconut shell fiber and corn straw fiber.

4. The environmentally friendly biodegradable modified composite material according to claim 3, characterized in that: The explosion pressure in the steam explosion treatment is 1.5-2.5 MPa, maintained for 10-15 seconds, and the fiber length after treatment is 0.5-2 mm, so as to improve the fiber dispersion and the interface bonding strength of the composite material.

5. The environmentally friendly biodegradable modified composite material according to claim 4, characterized in that: The concentration of the alkali solution in the alkali solution soaking treatment is 3%-5%, and the soaking time is 1-2 hours. The fiber is then rinsed with deionized water until it becomes neutral and dried to further remove impurities and pectin on the fiber surface and increase the roughness of the fiber surface.

6. The environmentally friendly degradable modified composite material according to claim 1, characterized in that: The auxiliary agent is maleic anhydride, 2-imidazolidinone and styrene and glycidyl acrylate copolymer, and the mass ratio of the three is 0.4:0.4:

1.

7. The environmentally friendly biodegradable modified composite material according to claim 1, characterized in that: The dosage of the silane coupling agent KH550 is 8%-12% of the mass of the nano-silicon dioxide, the working ultrasonic power of the ultrasonic cleaning machine is 300-500W, the processing time is 15-25 minutes, and the ultrasonic cavitation effect cooperates with the coupling agent to make the coupling agent more evenly coat the particle surface, form a stable chemical bonding layer, enhance compatibility with the matrix and interface adhesion, improve the tensile strength, elongation at break and thermal stability of the composite material, inhibit the generation of material defects caused by nano-particle agglomeration, and ensure the uniformity of the material microstructure and the consistency of macroscopic performance.

8. The environmentally friendly degradable modified composite material according to claim 1, characterized in that: The inorganic mineral filler is any one or more combinations of talc, calcium sulfate, calcium silicate and calcium carbonate, and has a particle size of 800-3000 mesh. This particle size range is conducive to its uniform dispersion in the matrix, reducing defects caused by agglomeration, enhancing the mechanical properties and stability of the material, ensuring that the degradation process is uniform, and avoiding the degradation rate and product life affected by local structural differences.

9. A method for preparing the environmentally friendly degradable modified composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1 Raw material pretreatment: Place polylactic acid in a vacuum drying oven and maintain it at 45-50°C for 4-5 hours to remove moisture and volatiles to prevent hydrolysis from causing molecular chain breakage and reducing performance; preheat inorganic mineral fillers and nano-silicon dioxide at 100-110°C for 30-35 minutes to improve their dispersibility and reactivity in the mixed system; natural plant fibers are pretreated by steam explosion and mixed with 60%-70% ethanol solution for 20-30 minutes to achieve initial dispersion and surface infiltration, which is conducive to subsequent uniform mixing with other raw materials; S2 premixing: weigh polybutylene adipate / terephthalate, dried polylactic acid, polybutylene succinate, preheated inorganic mineral filler, treated flax fiber, degradable polyester elastomer, modified nano-silica, tributyl citrate and additives according to proportion and put them into a high-speed mixer, mix them at a high speed of 500-900rpm for 7-8 minutes, use strong shear force to break the agglomeration of raw materials, and preliminarily evenly disperse the components; S3 secondary premixing: Add the additives again and premix for 5-6 minutes at a medium speed of 240-260rpm to optimize the uniformity of raw material distribution, ensure that the additives fully interact with the raw materials, and improve the compatibility of the system; S4 Melting, plasticizing and molding: The mixed material is fed into a co-rotating twin-screw extruder, and the screw temperature is set at 60-180°C, the screw speed is 150-250rpm, and the screw aspect ratio is 48:1-56:

1. Under this condition, the raw materials are fully melted, plasticized, mixed evenly, and extruded stably; the extruded strips are air-cooled and drawn, cut into pellets with a spacing of 4.6-4.8mm, vibrated and screened, and transported to the finished product silo.

10. Use of the environmentally friendly degradable modified composite material according to any one of claims 1 to 8 in the preparation of packaging bags, disposable tableware and agricultural mulch films.

Citation Information

Patent Citations

  • Biodegradable mulch and preparation method thereof

    CN105542423A

  • Full-biodegradable plastic composite modified material suitable for film bag and preparation method of full-biodegradable plastic composite modified material

    CN113956623A

  • Biodegradable nano composite material as well as preparation method and application thereof

    CN117986825A

Cited By

  • Preparation method of tertiary amine modified polyester capable of being rapidly degraded

    CN120118299B

  • Nano-modified spectacle wiping sheet packaging material and application thereof

    CN120156169A

  • Method and matched device for preventing fruit tree from fruit cracking

    CN120513803A

  • Environment-friendly degradable modified composite material, preparation method and application

    CN120665405A

  • Environment-friendly degradable modified composite material, preparation method and application

    CN120665405B